Clinical and genetic spectrum of SCN2A-associated episodic ataxia. (May 2019) - Schwarz, N.; Bast, T.; Gaily, E.; Golla, G.; Gorman, K.M.; Griffiths, L.R.; Hahn, A.; Hukin, J.; King, M.; Korff, C.; Miranda, M.J.; Møller, R.S.; et al.
Abstract: Background: Pathogenic variants in SCN2A are associated with various neurological disorders including epilepsy, autism spectrum disorder and intellectual disability. Few reports have recently described SCN2A -associated episodic ataxia (EA). Our study identifies its broader clinical and genetic spectrum, and describes pharmacological approaches. Results: We report 21 patients with SCN2A -associated EA, of which 9 are unpublished cases. The large majority of patients present with epileptic seizures (18/21, 86%), often starting within the first three months of life (12/18, 67%). In contrast, onset of episodic ataxia ranged from 10 months to 14 years of age. The frequency of EA episodes ranged from brief, daily events up to 1–2 episodes per year each lasting several weeks. Potential triggers include minor head traumas and sleep deprivation. Cognitive outcome is favorable in most patients with normal or mildly impaired cognitive development in 17/21 patients (81%). No clear genotype–phenotype correlations were identified in this cohort. However, two mutational hotspots were identified, i.e. 7/21 patients (33%) harbor the identical pathogenic variant p.A263V, whereas 5/21 (24%) carry pathogenic variants that affect the S4 segment and its cytoplasmic loop within the domain IV. In addition, we identified six novel pathogenic variants in SCN2A . While acetazolamide was previously reported as beneficial in SCN2A -associated EA in one case, our data show a conflicting response in 8 additional patients treated with acetazolamide: three of them profited from acetazolamide treatment, while 5/8 did not. Conclusions: Our study describes the heterogeneous clinical spectrum of SCN2A -associated EA, identifies two mutational hotspots and shows positive effects of acetazolamide in about 50%. Highlights: Pathogenic variants in SCN2A are associated with episodic ataxia (EA). EA is often accompanied by early-infantile onset epilepsy. Developmental outcome is favorable in most of these patients. Two mutational hotspots for SCN2A -associated EA were identified. Acetazolamide shows positive treatment effects in around half of the patients.